Non-utilization of selected newborn postnatal care and associated factors among postpartum women in East Africa: a multilevel mixed-effect analysis using the most recent DHS data 2016–2023 - Berhan Tekeba; Tadesse Tarik Tamir; Alebachew Ferede Zegeye (BMC Pregnancy and Childbirth)
Abstract Introduction Selected newborn postnatal care refers to selected early postnatal care within the first two days after birth, which can prevent up to 40% of neonatal death. Annually, over one million neonates die soon after birth every year worldwide, with sub-Saharan African countries, particularly east African countries, bearing a disproportionate burden. Despite the importance of these interventions, there is limited up-to-date information on the determinants of non-utilization of selected newborn postnatal care among postpartum women in East Africa. Therefore, this study aimed to assess the determinants of non-utilization of selected newborn postnatal care in East African countries using the most recent demographic and health care survey data (DHS) from 2016 to 2023. Methods The Demographic and Health Survey secondary data (DHS) reported from 2016 to 2023 in eleven East African countries was used. This secondary data was accessed from the DHS portal through an online request. The DHS is the global data collection initiative that provides detailed and high-quality data on population demographics, health, and nutrition in low- and middle-income countries. The analysis was conducted using a total weighted sample of 46,904 woman-child pairs who gave birth two years prior to the survey. Factors were selected based on a combination of theoretical relevance, empirical evidence, and statistical criteria. A multilevel mixed-effect binary logistic regression model was fitted to identify significant factors associated with non-utilization of selected newborn postnatal care. A bivariable analysis was done, and variables that had a p-value less than 0.2 were considered for multivariable analysis. In multivariable analysis, variables that had a p-value < 0.05 declared statistical significance. Result The pooled prevalence of non-utilization of selected newborn postnatal care in East Africa was 43.28% (95% CI 42.12–43.01). After adjusting for confounders, newborns from uneducated women (AOR = 2.04, 95% CI: 1.87–2.23), newborns from mothers with primary education (AOR = 1.23, 95% CI: 1.15–1.32), newborns from an uneducated father (AOR = 1.69, 95% CI: 1.56–1.84), newborns from fathers with primary education (AOR = 1.25, 95% CI: 1.17–1.33), newborns from working mothers (AOR = 1.25, 95% CI: 1.19–1.32), newborns from the poorest households (AOR = 1.49, 95% CI: 1.35–1.65), newborns from poor households (AOR = 1.26, 95% CI: 1.16–1.37), and newborns from countries in the lowest economic level (AOR = 1.56, 95% CI: 1.44–1.68) were positively associated with non-utilization of selected early postnatal care services in East Africa. Newborns from mothers with optimal ANC visits (AOR = 0.82, 95% CI: 0.78–0.86), newborns from mothers with media exposure (AOR = 0.66, 95% CI: 0.63–0.70), newborns delivered in health facilities (AOR = 0.23, 95% CI: 0.22–0.25), newborns from urban residences (AOR = 0.8, 95% CI: 0.74–0.86), and newborns delivered through cesarean section (AOR = 0.45, 95% CI: 0.40–0.50) were negatively associated with non-utilization of selected newborn postnatal care in East Africa. Conclusion This study highlights that a significant proportion of newborns in East Africa do not receive selected newborn postnatal care within two days after birth. To address this, governments, policymakers, and all other relevant authorities must prioritize initiatives to improve the utilization of selected postnatal care in East Africa, including promoting paternal and maternal education, strengthening ANC use, enhancing media use, improving health facility delivery, and fostering long-term economic development. Special attention should be given to working mothers.